ChemInform Abstract: Anionic N‐Heterocyclic Carbenes: Synthesis, Coordination Chemistry and Applications in Homogeneous Catalysis. Issue 32 (22nd July 2016) - Nasr, Alexandre; Winkler, Andrea; Tamm, Matthias
Abstract: Review: 304 refs.